Compression neuropathies of the forearm: anatomy, clinical features and management. (2nd August 2021) - Scarborough, Alexander; MacFarlane, Robert J; Klontzas, Michail; Zhou, Rui; Waseem, Mohammad
Abstract : The upper limb consists of four major parts: a girdle formed by the clavicle and scapula, the arm, the forearm and the hand. Peripheral nerve lesions of the upper limb are divided into lesions of the brachial plexus or the nerves arising from it. Lesions of the nerves arising from the brachial plexus are further divided into upper (proximal) or lower (distal) lesions based on their location. Peripheral nerves in the forearm can be compressed in various locations and by a wide range of pathologies. A thorough understanding of the anatomy and clinical presentations of these compression neuropathies can lead to prompt diagnosis and management, preventing possible permanent damage. This article discusses the aetiology, anatomy, clinical presentation and surgical management of compressive neuropathies of the upper limb.